The effect of career guidance in secondary schools on skills development and sustained economic participation: meaningful employment - Ntholeng, Mpho Gift (Graduate School of Business (GSB), 2025)
This study addresses the persistent gap between education and workforce needs in South Africa, contributing to structural unemployment. Focusing on the role of career guidance in secondary schools, the research examines its impact on skills development and its potential to bridge workforce skills gaps. The study aligns with Meyer's (2017) definition of structural unemployment and emphasises the need for targeted interventions during the secondary school-to-employment transition. The research explores the subject of “The Effect of Career Guidance in Secondary Schools on Skills Development and Sustained Economic Participation: Meaningful Employment." By analysing students' perceptions against labour market realities, the study aims to shed light on the multifaceted relationship between career guidance, skills development, and sustained economic participation. Using an exploratory sequential research design, the study employs interviews, some statistical analysis, and surveys. Qualitative data explores skills development and career guidance phenomena, while quantitative data provides insights into identified relationships. The integrated data analysis, following Sandelowski's (2000) approach, seeks to contribute new knowledge on the impact of career guidance on skills development and its alignment with labour market requirements. The study's findings confirm the crucial role of early and comprehensive career guidance in shaping students' future prospects. It reveals that students from lower quintile schools often lack exposure to various career options, limiting their ability to align their skills and interests with labour market demands. The absence of adequate career guidance contributes significantly to structural unemployment. The study advocates for proactive career guidance starting from grade 9 and underscores the importance of equipping schools with the necessary resources to provide effective career guidance. Ethical considerations included obtaining written consent and securing ethical clearance. This study not only advances theoretical frameworks but also provides practical insights for policymakers, educators, and practitioners to enhance career guidance programs and address the complex challenges of youth unemployment.